Synthesis and characterization of rhombic dodecahedral YAG microcrystals with good dispersity, high crystallinity and controllable crystal size1. Issue 48 (21st November 2018) - Yuan, Rui; Xie, Xi-Xi; Zheng, Li-Xian; Yu, Li-Li; Hu, Jian-Feng; Qin, Hai-Ming; Zhang, Zhi-Jun; Zhao, Jing-Tai
Abstract : Symmetrical rhombic dodecahedral YAG microcrystals were successfully prepared using improved hydrothermal methods. Abstract : By exploring the optimal reaction temperature and the ratio of Na2 SO4 to the precursor, highly symmetrical rhombic dodecahedral yttrium aluminum garnet (Y3 Al5 O12, YAG) microcrystals with a good dispersity were successfully prepared using improved hydrothermal methods. YAG microcrystals exhibit well-developed crystal faces, high crystallinity and a controllable crystal size, from hundreds of nanometers to approximately 4 μm. The morphology and crystal size of the YAG microcrystals can be controlled by changing the reaction temperature and the ratio of Na2 SO4 to the precursor. After analysis using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and energy dispersive spectrometry (EDS), the growth mechanism of the YAG crystals was studied in detail. Cerium doped YAG (YAG:Ce 3+ ) microcrystals exhibit an intense broad band emission at approximately 523 nm. Considering the high crystallinity, controllable size and strong emission of YAG microcrystals, one has reason to assume that they could have wide applications in many areas.